2015
DOI: 10.1096/fj.15-274944
|View full text |Cite
|
Sign up to set email alerts
|

Lithium chloride modulates chondrocyte primary cilia and inhibits Hedgehog signaling

Abstract: Lithium chloride (LiCl) exhibits significant therapeutic potential as a treatment for osteoarthritis. Hedgehog signaling is activated in osteoarthritis, where it promotes chondrocyte hypertrophy and cartilage matrix catabolism. Hedgehog signaling requires the primary cilium such that maintenance of this compartment is essential for pathway activity. Here we report that LiCl (50 mM) inhibits Hedgehog signaling in bovine articular chondrocytes such that the induction of GLI1 and PTCH1 expression is reduced ​ by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
57
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 71 publications
(104 reference statements)
6
57
0
Order By: Relevance
“…)24. As expected24, LiCl caused a decrease in GSK3B expression. Inhibition of GSK3B is associated with the activation of canonical Wnt signaling, and in both LiCl treated cells and IS cells there was an increase in beta-catenin expression (3.4-fold and 5.8-fold respectively).…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…)24. As expected24, LiCl caused a decrease in GSK3B expression. Inhibition of GSK3B is associated with the activation of canonical Wnt signaling, and in both LiCl treated cells and IS cells there was an increase in beta-catenin expression (3.4-fold and 5.8-fold respectively).…”
Section: Resultssupporting
confidence: 82%
“…Primary human osteoblast cells from the control group were treated with 10 mM LiCl, for 24 h (Based on work by Thompson et al . )24. As expected24, LiCl caused a decrease in GSK3B expression.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Arl13b is a key regulator of the ciliary trafficking of Hedgehog proteins (Caspary et al, ; Larkins et al, ; Mariani et al, ). Moreover, we have recently demonstrated that alterations in cilia length and Arl13b cilia localization are associated with altered Hedgehog signaling in chondrocytes (Thompson et al, ). Hedgehog signaling was therefore, examined in AKU and +HGA chondrocytes under basal conditions and in response to recombinant Indian Hedgehog (Ihh) using real time PCR.…”
Section: Resultsmentioning
confidence: 97%
“…In addition to regulation of TGFβ signalling, primary cilia also regulate a number of other osteogenic signalling pathways, such as Wnt [20], [43], runx2 [44], and hedgehog [45], [46]. Indeed, previous studies from Knight’s group have shown that changes in primary cilia length can modulate both hedgehog and Wnt signalling pathways [20], [42], [44], [45].…”
Section: Discussionmentioning
confidence: 99%